PEMBELAJARAN DALAM KALANGAN ORANG ASLI JAKUN KAMPUNG PETA MENERUSI PEMBANGUNAN EKOPELANCONGAN - Abdul Razzaq, Abdul Rasid; Bokhari, Norzella (Online Journal for TVET Practitioners, 2018)
Learning is considered as the acquisition of information and knowledge, the mastery of skills and habits, as well as forming attitudes and beliefs.Learning brings changes in a person, whether change for the better or the worse.It does not exclude adult learning where it is considered a continuing learning that is going on for a lifetime.A study was conducted at Kampung Peta, Kluang, Johor to explore and deeply understand the learner that they are going through as a result of the development in tourism activities at the TNJER area.For that purpose, a total of five study participants were selected based on the experiences of those who were directly involved with the ecotourism and homestay operators by using purposive sampling techniques.The semi structural interview method was selected for the data collection as this method provides the researchers with more space to deeply questioning the participants in the study.The interview data is compiled and coded using the thematic method of analysis to manage themes and categories.The findings show the natives community in Kampung Peta through learning processes in developing the Homestay Program and their participation in ecotourism activities.Learning to nature is crucial in everyday life of an indigenous community that sticks to their beliefs.